Career and work-family relationship among academics : An exploratory study - Santos, Gina Gaio (2016)
Despite the increase, in recent years, of women’s participation in the labour market, sex discrimination remains a reality in most work organisations. In this matter, academic organisations are no exception. Evidence of sex inequalities is well documented in the literature. At the individual level, inequalities are partly explained by family responsibilities mainly held by women. Having to spend a considerable amount of time in home and children related activities women are left with less time available for scientific work than their male colleagues. With the purpose of understanding how academics experience the relationship between work and family, 32 in-depth interviews were conducted among Portuguese academics of both sexes in one particular university. The findings confirmed that work-family conflict is stronger among female faculty than among their male counterparts. Additionally, the prejudice against maternity and the way it is compatible with a successful career appears to survive the new gender relations. Difficulties felt by female academics could be minimised by the introduction of «family-friendly» policies and the development of a positive organisational climate towards maternity and family issues.